Rearrangement of aniline(H2O)n (n = 0–12) clusters upon photoionization and their excited state properties: Density functional theory and time‐dependent density functional theory study. (26th May 2022) - Alauddin, Mohammad; Roy, Madhusudan; Song, Jae Kyu; Park, Seung Min
Abstract: We have studied H‐bonded structural rearrangement in the S0, S1, and D0 states of neutral and cationic aniline + (H2 O) n ( n  = 0–12) clusters by adopting density functional (DFT) and time‐dependent DFT (TD‐DFT) theory. DFT‐calculated structural rearrangement energies (SRE) increased sharply for n  = 1, 2, remained nearly the same until n  = 9, and increased again from n  = 10 to larger clusters. This indicates that the intramolecular vibrational modes play a central role in the rearrangement energy. On the other hand, DFT‐calculated thermochemical data confirmed that there is no significant change in enthalpy (H), Gibb's free energy (G), and entropy (S) for neutral and ionized clusters. The maximum UV absorption wavelength, λ max red‐shifted gradually with the increase of cluster size with respect to aniline as the hydration reduces the excitation energies. On the other hand, there was no significant change in the highest occupied molecular orbital (HOMO)‐lowest unoccupied molecular orbital (LUMO) energy gap. Abstract : The electronic transition of An(H2 O)12 cluster computed at 181.46 nm with oscillator strength of 0.4234 arises from HOMO‐1 to LUMO with the nature of π→π* electronic excitation